Stream pollution causes aggregation of wintering insectivorous birds through increased aquatic emergence - Lepori, Fabio (Frontiers in Ecology and Evolution, 2022)
Cross-boundary prey subsidies can propagate the effects of human impacts from streams to terrestrial ecosystems, but effects during winter are poorly known. Here I focused on this season and investigated the effects of pollution due to a sewage treatment plant (STP) on aquatic insect emergence and wintering insectivorous birds in a Swiss stream. At sites downstream of the STP, a combination of nutrient (phosphorus), organic pollution (biochemical oxygen demand), and thermal pollution led to higher aquatic emergence compared to upstream sites (6× higher). In turn, the higher emergence led to a strong aggregational response by wintering insectivorous birds (7× higher linear densities compared to upstream sites). Polluted sites also had a different bird assemblage, which included rare wintering species that forage largely on aerial insects. A comparison between the polluted (downstream) sites and a nearby unpolluted stream produced similar differences. The magnitude and consistency of the effects illustrate how strongly stream alterations can propagate to birds through changes in aquatic emergence. Moreover, the results provide insights into the responses of linked stream-terrestrial food webs to other environmental issues that cause warming and/or pollution, including urbanization and climate change.